STRATEGI GURU PAI DALAM MENGEMBANGKAN KECERDASAN SPIRITUAL SISWA SECARA DARING - K Komariah; H Hamdanah; S Surawan (Universitas Islam Sultan Agung, 2021)
This study aims to determine the strategy of Islamic Education teachers in developing students' spiritual intelligence online at SMAN 1 Pantai Lunci. This type of research is qualitative using descriptive qualitative methods. The subjects of this study were PAI teachers while the informants in this study were students, BK teachers, and parents of students. Data collection techniques using observation, interviews, documentation. The data validation technique used source triangulation and technique triangulation. The data analysis technique was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study indicate that the PAI teacher strategy in developing students' spiritual intelligence online at SMAN 1 Pantai Lunci is an independent learning strategy by going through several stages, namely determining learning objectives, delivering learning materials, and giving independent assignments in the form of summarizing the Angel Always with Me material which contains the value of faith and reading the Qur'an which contains the value of worship, then independent activities and the last stage is to do an evaluation.Keywords: Spiritual Intelligence, PAI Learning, Teacher Strategy